Issues of UK citizenship by British law (Journal of actual problems of jurisprudence, 2018)
The significance of citizenship in any legal system is of paramount and copious importance. This article discusses notion, the concept of citizenship and issues of citizenship around the UK legislation. Features of citizenship in the UK are appropriately disclosed. Particular attention is paid to the demands of taking British citizenship, to the privileges and consequences. The conclusion was that it is worth considering before getting new citizenship or acquiring foreign nationality.Key words: nationality, citizenship, allegiance, migration, British citizenship, naturalization, immigrants, belonging, ceremony, status.